Design of Structural Steel Pipe Racks - Drake, Richard M.; Walter, Robert M. (Engineering Journal, 2010)
Pipe racks are structures in petrochemical, chemical and power plants that are designed to support pipes, power cables and instrument cable trays. They may also be used to support mechanical equipment, vessels and valve access platforms. Pipe racks are non-building structures that have similarities to structural steel buildings. The design requirements found in the building codes are not clear on how they are to be applied to pipe racks. Several industry references exist to help the designer apply the intent of the code and follow expected engineering practices. This paper summarizes the building code and industry practice design criteria, design loads and other design consideration for pipe racks.